Portal Annular Pancreas. A Rare Variant and a New Classification - Joseph, Philip; Raju, Ravish Sanghi; Vyas, Frederick Lorence; Eapen, Anu; Sitaram, Venkatramani (JOP. Journal of the Pancreas, 2010)
Context Portal annular pancreas is a rare congenital anomaly resulting from fusion of the pancreatic parenchyma around the portal vein/superior mesenteric vein. It is asymptomatic, but could have serious consequences during pancreatic surgery, if unrecognized. We describe a variant of this anomaly encountered during pancreaticoduodenectomy and propose a new classification. Case report We report a 51-year-old male who underwent a pancreaticoduodenectomy for periampullary carcinoma. After division of the pancreatic neck, a sheath of tissue was found posterior and extending to the left of the portal vein. When we divided this tissue, a large duct was encountered; this duct communicated with the main pancreatic duct. On review of the CT images, the main pancreatic duct was seen to be passing posterior to the portal vein and a smaller accessory pancreatic duct was present anterior to the portal vein. We describe the surgical implications. Conclusion This variant of portal annular pancreas has not yet been reported during pancreaticoduodenectomy and we propose a new classification for this fusion anomaly. Image: Pancreatic ducts on either side of the portal vein.